Delivery of infection from asymptomatic carriers of COVID-19 in a familial cluster. (May 2020) - Ye, Feng; Xu, Shicai; Rong, Zhihua; Xu, Ronghua; Liu, Xiaowei; Deng, Pingfu; Liu, Hai; Xu, Xuejun
Highlights: There are more than 100, 000 confirmed COVID-19 cases, with spread to over 100 countries as of 2020-03-08. Asymptomatic carriers during the incubation period can be a potential infection source of COVID-19. Person-to-person transmission has been documented; asymptomatic carriers should be a focus for disease prevention. Abstract: Objectives: With the ongoing outbreak of COVID-19 around the world, it has become a worldwide health concern. One previous study reported a family cluster with an asymptomatic transmission of COVID-19. Here, we report another series of cases and further demonstrate the repeatability of the transmission of COVID-19 by pre-symptomatic carriers. Methods: A familial cluster of five patients associated with COVID-19 was enrolled in the hospital. We collected epidemiological and clinical characteristics, laboratory outcomes from electronic medical records, and also verified them with the patients and their families. Results: Among them, three family members (Case 3/4/5) had returned from Wuhan. Additionally, two family members, those who had not traveled to Wuhan, also contracted COVID-19 after contacting with the other three family members. Case 1 developed severe pneumonia and was admitted to the ICU. Case 3 and Case 5 presented fever and cough on days two through three of hospitalization and had ground-glass opacity changes in their lungs. Case 4 presented with diarrhea and pharyngalgia after admission without radiographic abnormalities. Case 2 presented no clinical nor radiographic abnormalities. All five cases had an increasing level of C-reactive protein. Conclusions: Our findings indicate that COVID-19 can be transmitted by asymptomatic carriers during the incubation period.